2022
DOI: 10.3389/fimmu.2022.901671
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Senescence Characteristics Defines a Novel Prognostic Signature to Guide Personalized Treatment for Clear Cell Renal Cell Carcinoma

Abstract: Accumulating evidence has suggested the impact of senescence on tumor progression, but no report has yet described how senescence shapes the tumor microenvironment of clear cell renal cell carcinoma (ccRCC). The objective of this study was to delineate the senescence features of ccRCC and its role in shaping the tumor microenvironment through a comprehensive analysis of multiple datasets, including 2,072 ccRCC samples. Unsupervised consensus clustering identified three senescence subtypes, and we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…This is one of the reasons why the C2 subtype has a worse prognosis than the C1 subtype. This phenomenon was consistent with previous reports that identified the manifestation of senescent subtypes of clear cell renal cell carcinoma (33).…”
Section: Gsva Analysis Of the Cs-enrichment Pathway Hallmarkssupporting
confidence: 94%
“…This is one of the reasons why the C2 subtype has a worse prognosis than the C1 subtype. This phenomenon was consistent with previous reports that identified the manifestation of senescent subtypes of clear cell renal cell carcinoma (33).…”
Section: Gsva Analysis Of the Cs-enrichment Pathway Hallmarkssupporting
confidence: 94%
“…The characteristic of tumor microenvironment strongly influence disease biology and may influence the response rate to systemic therapy. Targeted immunotherapy is currently an option in first line treatment because KIRC is also considered an immunogenic tumour with high numbers of immune cells ( 4 ). Macrophage infiltration in KIRC is associated with prognosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirmed the differential expression of MAP2K6 in KIRC, which suggests its possible involvement in the biological processes of ccRCC. Recent study confirms MAP2K6 as senescence-related genes in ccRCC may influence the efficacy of anti-PD-1 therapy and Sunitinib/Everolimus treatment (43). Related studies have confirmed that activation of the Ras-MAPK pathway promotes immune evasion of tumor cells, proving that many associated molecules of the MAPK signaling pathway are significantly correlated with immune cell infiltration.…”
Section: Discussionmentioning
confidence: 81%